The effects of sage essential oil on memory Impairment, anxiety and depression in the scopolamine rat model of Alzheimer’s disease - Akbaba, Emel Aydın; Bağcı, Eyüp; Hritcu, Lucian (My University, 2016)
Neuroprotective activities of the essential oil extracted from Salvia multicaulis (1% and 3%, for 21 continuous days), was studied by means of in vivo (Y-maze, radial arm-maze, elevated plus-maze and forced swimming tests) approaches in scopolamine (0.7 mg/kg, i.p.)-induced amnesia rat model. As expected, the scopolamine alone-treated rats exhibited the following: decrease of spontaneous alternation percentage in Y-maze test, increase of the number of working memory errors and the number of reference memory errors in radial arm-maze test along with decrease of the exploratory activity, the percentage of the time spent and the number of entries in the open arm within elevated plus-maze test and decrease of swimming time and increase of immobility time within forced swimming test. Dual scopolamine and Salvia multicaulis essential oil-treated rats showed significant improvement of memory formation and exhibited anxiolytic- and antidepressant-like effects in scopolamine-treated rats. These results suggest the neuroprotective potential of Salvia multicaulis essential oil in scopolamine-induced amnesia in rats and could act as a promising therapeutic agent for the neurological abnormalities related to Alzheimer's disease.
Bildiri - Yayımlanmış
Keywords: Anxiety; Depression; Sage essentiai oil; Spatial memory; Alzheimer’s disease